Impact of SiO2 nanoparticle morphology on scattering efficiency for random lasers - Machado, Yan D.R.; Germano, Gleice C.M.; Pecoraro, Edison [UNESP]; Costa, Antonio Mario L.M.; Carvalho, Isabel C.S. (Elsevier, 2024)
In this work, we compared the effect of Quartzite nanoparticles (QtzNP - crystalline SiO2) and amorphous silica nanoparticles (ASNP) as scatters in a random laser (RL), correlating the laser efficiency to the morphology, phase and refractive index (RI) of the scatterers. The RL was based on a laser media containing suspensions of QtzNPs or ASNPs in Rhodamine 6G (Rh6G) and ethylene glycol (EG) suspension. It was observed a considerable increase in RL efficiency for QtzNPs, as compared to ASNPs, even for concentrations as low as 0.5 mg/mL. Such grow in the RL efficiency is attributed to the higher RI of QtzNPs (n = 1.54), which increases the reflectance of light on the particles surface and the high field scattering intensity in the sharp edges of the flat slab shapes, associated to the particle's morphology, as well as a higher scattering cross section. Finite Element Method (FEM) simulations were also performed for different particle size and shapes and an output increase is noticed for QtzNPs when compared with the ASNP confirming the experimental results. The comparison between the morphology of QtzNPs and ASNPs on scattering efficiency reported here contribute to optimize the performance of laser systems with natural and synthetic nanomaterials.
Keywords: Finite element method; Quartzite; Random laser; Scattering; Silica